NONSTANDARD PROBLEMS IN STUDYING THE PROPERTIES FUNCTIONS - Kuzmich, B.I. (Journal of Information Technologies in Education (ITE), 2010)
In this paper we consider two non-standard problems that may be offered to students for independent solution in the study of fundamental properties of functions in the course of mathematical analysis. These tasks are wearing creativity and contribute to a better understanding of students to concepts such as monotonicity and continuity of the function